Study of the Antagonism of Biocontrol Strains Against the Blue-Stain Fungus of Rubberwood - Xiaolong Wu; Susu Yang; Jun Li; Jian Qiu; Lei Qin (Journal of Fungi)
Wood blue staining is one of the most common wood defects, which commonly occurs in rubberwood and Masson pine. It not only affects the appearance of the wood, but also its properties. In this study, rubberwood from Xishuangbanna was examined. During the process, blue-stain fungi and endophytic fungi were isolated and identified. The antagonism of biocontrol strains against blue-stain fungi was studied, and their inhibitory effects were evaluated by inoculating the biocontrol strains on non-blue-stained rubberwood. The morphology and distribution of the strains on the wood were observed using polarized light and fluorescence microscopy, infrared spectroscopy, scanning electron microscopy (SEM–EDS), and X-ray diffraction (XRD). The effects of biocontrol strains on the blue stain of the wood were then evaluated. The results showed that at room temperature, the fungus causing the blue stain in rubberwood was identified as Lasiodiplodia theobromae, and the biocontrol strains of endophytic fungi isolated were Trichoderma koningii and Trichoderma reesei. It was found that T. reesei was more effective than T. koningii in inhibiting the development of L. theobromae. Based on these findings, T. reesei was suggested as a biocontrol strain for preventing and controlling blue stain in rubberwood.